Ecological Niche Explains the Sympatric Occurrence of Lined Ground Snakes of the Genus Lygophis (Serpentes, Dipsadidae) in the South American Dry Diagonal - Ceron, Karoline; Mângia, Sarah; Guedes, Thaís B.; Alvares, Diego Janisch; Neves, Matheus O.; De Toledo Moroti, Matheus; Torello, Natália [UNESP]; Borges-Martins, Márcio; Ferreira, Vanda L.; Santana, Diego J. (Herpetologists League, 2021)
The geographic distribution of a species is limited by many factors, including its ecological and evolutionary history. Species distribution modeling has been used to evaluate the effects of climate and other variables on geographic distribution and to measure the degree of niche similarity among co-occurring species. Our goal in this study was to compare the geographic distributions and ecological niches of four closely related species of lined ground snakes, Lygophis dilepis, L. flavifrenatus, L. meridionalis, and L. paucidens. These species are distributed along the South American Dry Diagonal. We found that the four species of Lygophis overlap somewhat along their distributions with a low degree of niche overlap. Lygophis dilepis shows a disjunct distribution with two isolated populations. The break in the distribution of L. dilepis in Central Brazil is filled by L. meridionalis, which is found mostly in the highlands of the Central Plateau. Because of the disjunct distribution of L. dilepis, we performed species distribution modeling on both populations separately. The environmental niches of the two populations of L. dilepis were indistinguishable according to the niche equivalence tests, but the distribution of one of these populations did not predict the distribution of the second one, and vice versa. Our study shows that niche partitioning may allow for the coexistence of Lygophis species.
Keywords: Caatinga; Cerrado; Chaco; Geographic distribution; Potential distribution